Preschoolers' Helping Motivations: Altruistic, Egoistic or Diverse? - Hao, Jian; Du, Xu (Frontiers in Psychology, 2021)
Based on Eisenberg et al.’s model of prosocial motivations, the present study examined what motivates preschoolers to display instrumental helping and how various motivations develop during the preschool years. The participants were 477 preschoolers aged 3 to 5 years assigned to one of five groups. In each experimental group, the experimenter emphasized an altruistic or egoistic helping motivation, namely, empathic concern, moral rules, praise or rewards. In the control group, no helping motivations were emphasized. Their instrumental helping was then measured by sorting cards for a sick child to play a game. The results show that each helping motivation had a positive effect on instrumental helping. Most of the motivational effects were similar across age, but the motivational effect of empathic concern increased obviously at the age of 5 years. Therefore, the present study reveals that both altruistic and egoistic motivations motivate preschoolers to help others. Most of the motivations develop steadily during the preschool years, but empathic concern as an altruistic motivation increases greatly at the end of the preschool years. The present study thus confirms the diversity of preschoolers’ helping motivations with Eisenberg et al.’s model of prosocial motivations.